Enhanced levels of leukotriene B(4) in synovial fluid in Lyme disease - Mayatepek, E. (Hindawi Publishing Corporation, 1993)
The purpose of this study was to evaluate the potential role of LTB(4) and cysteinyl leukotrienes in Lyme disease (LD). Therefore, a total number of 34 patients divided into four groups was studied. The patients were classified as having Lyme arthritis (n = 7) or Lyme meningitis (n = 10), and as control groups patients with a noninflammatory arthropathy (NIA) (n = 7) and healthy subjects (n = 10). LTB(4) as well as LTC(4) secretion from stimulated polymorphonuclear leukocytes (PMNL) from all groups of patients showed no statistical differences. LTB(4) levels in synovial fluid were significantly increased in patients with Lyme arthritis (median 142 ng/ml, range 88–296) when compared to the control subjects with NIA (median 46 ng/ml, range 28–72) (p < 0.05). No statistical difference of urinary LTE(4) levels between all the different groups of patients was observed. These results show that cysteinyl leukotrienes do not play an important role in the pathogenesis of LD. In contrast to previous findings in rheumatoid arthritis, LTB(4) production from stimulated PMNL was not found to be increased in LD. However, the significantly elevated levels of LTB(4) in synovial fluid of patients with Lyme arthritis underline the involvement of LTB(4) in the pathogenesis of this disease.